MASS-MEDIA AND THE OLYMPIC MOVEMENT - LEUCIUC Florin-Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Media is an agent which concerns the implication in the promotion of the Olympic ideas. The information given by the mean of the press, radio and television contributed at the growth of the high reputation of the most important sportive competition of the year. Among these, television has the greatest contribution, and so the sums paid for the O.G.'s broadcasting grew dizzily in the late years. At the last editions of the O.G., there were covered, by live transmissions or recorded ones, all contest events. The last editions of the O.G., all the contest events have been covered by transmissions, live or recorded; the cover being almost global, they could be seen by 90% of the Earth population.